Barriers and facilitators to writing quality items for medical school assessments – a scoping review - Sowmiya Karthikeyan; Elizabeth O’Connor; Wendy Hu (BMC Medical Education, 2019)
Abstract Background Producing a sufficient quantity of quality items for use in medical school examinations is a continuing challenge in medical education. We conducted this scoping review to identify barriers and facilitators to writing good quality items and note gaps in the literature that are yet to be addressed. Methods We conducted searches of three databases (ERIC, Medline and Scopus) as well as Google Scholar for empirical studies on the barriers and facilitators for writing good quality items for medical school examinations. Results The initial search yielded 1997 articles. After applying pre-determined criteria, 13 articles were selected for the scoping review. Included studies could be broadly categorised into studies that attempted to directly investigate the barriers and facilitators and studies that provided implicit evidence. Key findings were that faculty development and quality assurance were facilitators of good quality item writing while barriers at both an individual and institutional level include motivation, time constraints and scheduling. Conclusions Although studies identified factors that may improve or negatively impact on the quality of items written by faculty and clinicians, there was limited research investigating the barriers and facilitators for individual item writers. Investigating these challenges could lead to more targeted and effective interventions to improve both the quality and quantity of assessment items.